The role of cognitive psychology, internal conditions, and technology utilization in shaping accounting behavior of SMEs - Ridhawati, Rini; Suryantara, Adhitya Bayu; Nurabiah, Nurabiah; Indriani, Eni (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study aims to investigate the influence of intrapersonal (cognitive) factors, internal business conditions, and technology integration in operations on accounting behavior among MSMEs. This study uses a two-phase sequential quantitative design, comprising two tests: the Binary Logistic Regression Test to determine the relationship between internal condition factors and accounting adoption, and the SEM-PLS Test to examine the influence of cognitive ease on the utilization of accounting information, including IMR as a control variable. Initial data were obtained through distributing questionnaires to 250 MSMEs in Mataram City, selected using purposive sampling. The results of this study indicate that there is a relationship between the variables of third-party credit and digital payments on the preparation of accounting information. Meanwhile, the variables of business age, business form, and accounting training have no relationship with the preparation of accounting information. Furthermore, it is known that there is a positive influence between repeated experience and the utilization of accounting information. In contrast, the variable of avoiding strain has no effect on the utilization of accounting information in the MSMEs studied.